Vitamin D deficiency increases the risk of bacterial vaginosis during pregnancy: Evidence from a meta-analysis based on observational studies - Ma, Lirong; Zhang, Zhuoran; Li, Liyang; Zhang, Lijie; Lin, Zhijuan; Qin, Hao (Frontiers in Nutrition, 2022)
Background: Bacterial vaginosis (BV) is the most common microbiological syndrome in women of childbearing age, causing numerous adverse health issues in pregnant women. Several observational studies have discussed the association between vitamin D deficiency and the risk of BV during pregnancy, but the results were inconclusive. Therefore, this meta-analysis aimed to explore the association between vitamin D deficiency and BV risk in pregnant women. Methods: We searched four databases, including PubMed, Embase, Cochrane Library, and Web of Science, from their inception to July 2022. Pooled odds ratios (OR) with corresponding 95% confidence intervals (CI) were estimated using random effects models. Additionally, we conducted subgroup analyses to identify the potential sources of between-study heterogeneity. Sensitivity analysis was performed using the method of exclusion, one study at a time. Publication bias was examined using Egger’s test and funnel plot. Results: A total of 14 studies from 13 articles including 4793 participants were eligible for this meta-analysis. The outcome showed that vitamin D deficiency may increase the risk of BV during pregnancy by 54% (OR, 1.54; 95% CI, 1.25-1.91; P<0.001). In subgroup analyses, positive associations were also found in studies that were: conducted in black women (OR, 1.56; 95% CI, 0.98-2.48; P=0.060), focused on the first trimester of pregnancy (OR, 2.22; 95% CI, 1.35-3.64; P=0.002), of high quality (OR, 3.05; 95% CI, 1.26-7.41; P=0.014), and adjusted for confounders (OR, 1.28; 95% CI, 1.06-1.55; P=0.012). Sensitivity analysis reported that BV risk during pregnancy resulting from vitamin D deficiency increased by 157% (OR, 2.57; 95% CI, 1.50-4.42; P=0.001) when removing the first two high-weight studies. Publication bias was observed using Egger’s test (t=3.43, P=0.005) and a visual funnel plot. Conclusions: This meta-analysis showed that vitamin D deficiency is positively associated with the risk of BV during pregnancy. Further high-quality prospective cohort studies are needed to determine whether vitamin D intake reduces the prevalence of BV in pregnant women.